2005
DOI: 10.1007/s11630-005-0004-4
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady tip clearance flow in an isolated axial compressor rotor

Abstract: The paper investigates effects of operating conditions, tip clearance sizes and external unsteady excitations on the unsteady tip clearance flow in an isolated axial compressor rotor by unsteady 3D Navier-Stokes simulations. The results show that the unsteady tip clearance vortex takes a periodic flow behavior in the rotor tip region. With the decrease of the flow coefficient, the unsteady tip clearance vortex is enhanced and its frequency becomes lower. A larger tip clearance size can cause bigger unsteady fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
4
22
0
3
Order By: Relevance
“…Several peaks of considerable magnitudes can be observed at each chordwise position, indicating the occurrence of the spike stall. This conclusion is in a good agreement with the results of Zhang et al 13 and Vo et al, 15 which have shown that the periodic characteristics of the tip leakage flow can be recognized by existence of some peaks in the frequency spectrum at the near-stall condition. Zhang et al 13 have shown that the self-induced unsteadiness is caused by the interaction of the main inflow with the tip leakage flow and fluctuates with a frequency lower than the blade passing frequency.…”
Section: Frequency Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Several peaks of considerable magnitudes can be observed at each chordwise position, indicating the occurrence of the spike stall. This conclusion is in a good agreement with the results of Zhang et al 13 and Vo et al, 15 which have shown that the periodic characteristics of the tip leakage flow can be recognized by existence of some peaks in the frequency spectrum at the near-stall condition. Zhang et al 13 have shown that the self-induced unsteadiness is caused by the interaction of the main inflow with the tip leakage flow and fluctuates with a frequency lower than the blade passing frequency.…”
Section: Frequency Analysissupporting
confidence: 92%
“…Hence, in addition to performing various kinds of casing treatments in enhancing the compressor stall margin, some researchers like Rae and Breuer, 11 Mailach et al 12 and Zhang et al 13 focused on studying the characteristics of this complex flow in details. Some investigations have been carried out to study the relation between the unsteady tip leakage flow and the spike stall inception as precursor of the fully developed rotating stall.…”
Section: Introductionmentioning
confidence: 99%
“…With tip clearance of 2.2% tip chord the region of influence by the tip leakage flow not only reaches the pressure side of the neighboring blade, but also penetrates further down along the span of the blade. According to reference [6,10], self-induced unsteadiness of tip leakage flow appears when tip leakage flow is strong enough to change the original pressure distribution on adjacent blade pressure surface. It is therefore not surprised that only the case with 2.2% tip chord exhibits the unsteadiness at this mass flow rate, while the other two cases are steady.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [6] demonstrated tip leakage vortex became unsteady at high loading operating conditions with relatively large tip clearance in a low-speed compressor rotor. When studying a high-speed compressor rotor, Yamada et al [7] found that breakdown of tip leakage vortex occurring in the compressor rotor resulted in self-sustained flow oscillation in the tip leakage flow field at near-stall operating condition as well as at near peak efficiency condition.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there are three different views about the occurrence of unsteadiness of tip clearance flow. Mailach et al [3] has shown that the investigated low speed compressor develops a two passage periodic tip leakage vortex pattern, which is called 'rotating instabilities' .Zhang et al [4] and Tong et al [5] found that prior to the initiation of spike inception, the tip leakage flow shows obvious self-induced unsteadiness caused by the fluctuation of the pressure difference across the tip clearance in their computational and experimental work, respectively. Such unsteadiness has been proved to have some relations with the initiation of a spike inception by Lin et al [6].…”
Section: Introductionmentioning
confidence: 99%